Primary refractory follicular lymphoma: a poor outcome entity with high risk of transformation to aggressive B cell lymphoma. (November 2021) - Alonso-Álvarez, Sara; Manni, Martina; Montoto, Silvia; Sarkozy, Clémentine; Morschhauser, Franck; Wondergem, Marielle J.; Guarini, Attilio; Magnano, Laura; Alcoceba, Miguel; Chamuleau, Martine; Galimberti, Sara; Gomes da Silva, Maria; et al.
Abstract: Background: Primary refractory (PREF) follicular lymphoma (FL) has a completely different clinical course from that of FL that responds to front-line treatments. In addition to having poor responses to salvage therapies, it seems that patients with PREF are at increased risk of histological transformation (HT). The Aristotle consortium presented the opportunity of investigating the risk of HT in a very large series of cases. Thus, we investigated the risk of HT in patients with PREF FL compared with that of responding patients or in stable disease and ultimately their outcome. Methods: Six thousand three hundred thirty-nine patients from the Aristotle database were included in the analysis. These patients had a histologically confirmed grade 1, 2 or 3a FL diagnosed between 1997 and 2013. The primary end-points were the cumulative incidence (CI) of HT at the first progression or relapse and the survival after transformation. Findings: The 5-year CI of HT among patients with PREF was 34% (95% confidence interval (CI): 27–43), whilst it was 7.1% (95% CI: 6.0–8.5) in the group of patients with partial response (PR) or stable disease (SD) (PR + SD) and 3.5% (95% CI: 3.0–4.2) in the group of patients achieving complete response (CR). The 5-year survival after relapse (SAR) was 33% (95% CI: 28–39) for the PREF group, 57% (95% CI 54–61) in patients with PR, 51% (95% CI 43–58) in the SD group after first-line therapy and 63% (95% CI: 66–72) in patients with CR after initial treatment ( p -value <0.001). The 5-year SAR for those patients with PREF who developed HT was 21% (95% CI: 12–31), clearly diminished when compared with those patients with PREF who did not experience HT (38% [95% CI: 31–44]) ( p -value = 0.001). Interpretation: Patients with PREF FL have a dismal outcome and an associated very high rate of HT that further worsens their poor prognosis. Highlights: Five per cent of patients with follicular lymphoma (FL) were primary refractory to initial treatment. These patients have increased risk of developing histological transformation (HT). HT in this group of patients worsens their already poor survival. Hidden transformation at diagnosis should be investigated in this group of patients.